Metabolite Profiling of the Plasma and Leukocytes of Chronic Myeloid Leukemia Patients - Karlíková, Radana; Široká, Jitka; Friedecký, David; Faber, Edgar; Hrdá, Marcela; Mičová, Kateřina; Fikarová, Iveta; Gardlo, Alžběta; Janečková, Hana; Vrobel, Ivo; Adam, Tomáš (Journal of proteome research, 2016)
The discovery of tyrosine kinase inhibitors (TKIs) brought a major breakthrough in the treatment of patients with chronic myeloid leukemia (CML). Pathogenetic CML events are closely linked with the Bcr-Abl protein with tyrosine kinase activity. TKIs block the ATP-binding site; therefore, the signal pathways leading to malignant transformation are no longer active. However, there is limited information about the impact of TKI treatment on the metabolome of CML patients. Using liquid chromatography mass spectrometric metabolite profiling and multivariate statistical methods, we analyzed plasma and leukocyte samples of patients newly diagnosed with CML, patients treated with hydroxyurea and TKIs (imatinib, dasatinib, nilotinib), and healthy controls. The global metabolic profiles clearly distinguished the newly diagnosed CML patients and the patients treated with hydroxyurea from those treated with TKIs and the healthy controls. The major changes were found in glycolysis, the citric acid cycle, and amino acid metabolism. We observed differences in the levels of amino acids and acylcarnitines between those patients responding to imatinib treatment and those who were resistant to it. According to our findings, the metabolic profiling may be potentially used as an additional tool for the assessment of response/resistance to imatinib.
Keywords: Plasma; metabolomics; inhibitory proteinkinas; lidé; Hydroxyurea; Metabolomics; Amino Acids; tyrosine kinase inhibitors; Glycolysis; chronic myeloid leukemia; metabolom; metabolomika; aminokyseliny; krevní plazma; Humans; hydroxyurea; imatinib mesylát; chronická myeloidní leukemie; Metabolome; glykolýza; Citric Acid Cycle; monitorování léčiv; citrátový cyklus; drug resistance; Protein Kinase Inhibitors; Drug Monitoring; Leukocytes; hydroxymočovina; Leukemia, Myelogenous, Chronic, BCR-ABL Positive; leukocyty; Imatinib Mesylate